2008
DOI: 10.1097/opx.0b013e31818527cd
|View full text |Cite
|
Sign up to set email alerts
|

Management of Evaporative Dry Eye in Ectrodactyly-Ectodermal Dysplasia-Clefting Syndrome

Abstract: Low dose lipid base ointment application may be a promising treatment modality for the ocular surface disease in ectrodactyly-ectodermal dysplasia (EEC)-clefting syndrome, which seems to help in alleviating the subjective complaints and in improving the objective clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…The absence of the meibomian glands leads to an instability of the tear film, with a normal Schirmer test but pathological BUT. Lemp [24] reported that patients with absent or deficient meibomian gland function should be categorized in the evaporative group of dry eye syndromes [15]. Matsumoto et al [13] measured the tear evaporation rate to clarify the changes in tear quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of the meibomian glands leads to an instability of the tear film, with a normal Schirmer test but pathological BUT. Lemp [24] reported that patients with absent or deficient meibomian gland function should be categorized in the evaporative group of dry eye syndromes [15]. Matsumoto et al [13] measured the tear evaporation rate to clarify the changes in tear quality.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Schirmer I test was 5/6 mm and BUT 6/6 s in one patient, he had no dry eye complaints. The authors attributed the corneal abnormalities to an unstable tear film due to a lack of lipid secondary to absence of meibomian glands and goblet cell abnormalities [15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of this rare autosomal recessive hereditary disease include abnormalities of the epidermis and its appendages (hair, nails, eccrine and sebaceous glands) together with lack of sweat glands or more frequently decrease in sweat glands which leads to increase in body temperature (1). Ocular findings including strabismus, telecanthus, blepharophymosis, entropion, dacriocystitis, blepharitis, conjunctivitis, meibomian gland dysfunction, corneal opacity and cataract may be observed in individuals with ectodermal dysplasia (3)(4)(5)(6)(7)(8)(9). Recurring corneal erosions, opacifications, vascularization and perforations affect various ocular surface disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recurring corneal erosions, opacifications, vascularization and perforations affect various ocular surface disorders. However, the reason of ocular surface disorders in individuals with ectodermal dysplasia is not known exactly (6,7). To prevent corneal demage these patients should be followed up with artificial tear.…”
Section: Introductionmentioning
confidence: 99%